Design Android-Based Mobile Food Vendor Location Search Application - Nadia Bintang; Sumpena Sumpena; Wawan Setiawan; Agung Raharja (Journal of Computer Science Advancements, 2024)
The development of culinary business in Indonesia is progressing from time to time. This was helped by the development of increasingly rapid technology. Non-formal business actors also develop, especially mobile food vendors. The author wants to create an application that can improve the competitiveness of mobile food vendors by providing information that is easily obtained by the public to find out information and locations of mobile food vendors that can be accessed via mobile devices connected to the internet. This research offers an android application that can track the presence of traders in realtime making it easier for users to find food vendors around them using the Location Based Service (LBS) method using Global Positioning System (GPS) technology. In addition, this application also uses Google Maps API technology for map and Firebase needs for database needs.